Analisis Pengaruh Kinerja Keuangan Terhadap Tingkat Bagi Hasil Deposito Mudharabah Pada Bank Umum Syariah Di Indonesia Tahun 2012–2018 - Nia Sulfiani; Rimi Gusliana Mais (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2019)
This study aims to determine the effect of Return On Assets (ROA), Financing to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), Operating Costs to Operating Income (BOPO), and Non-Performing Financing (NPF) on Profit Sharing Rates for Mudharabah Deposits. at Islamic Commercial Banks in Indonesia in 2012–2018. The results of the analysis show that the Capital Adequacy Ratio (CAR) has a negative and significant effect on the Profit Sharing Rate for Mudharabah Deposits, which means that no matter how big the CAR value of a Sharia Commercial Bank (BUS) company is, it will result in a lower Profit Sharing Rate for Mudharabah Deposits. Return on Assets (ROA), Financing to Deposit Ratio (FDR), Operating Costs to Operating Income (BOPO), and Non Performing Financing (NPF) have no effect on the Profit Sharing Rate for Mudharabah Deposits, which means no matter how big the ROA, FDR, BOPO, and NPF will not affect profit investment, loan disbursement, operating costs and income, non-performing financing to the rate of profit sharing for mudharabah deposits.